Konsep Diri Ceu Epik Sebagai Food Influencer dengan Kearifan Lokal di Tiktok - Zalfa Dzihni Aulia; Lusy Mukhlisiana (Universitas Prof. Dr. Moestopo (Beragama), 2026)
This study examines the self-concept of Ceu Epik as a food influencer who carries local wisdom on TikTok, a phenomenon reflecting how ordinary individuals construct digital identities rooted in cultural authenticity. The research problem centers on how self-concept is formed and expressed through content creation in a local culinary context. This study uses a qualitative descriptive research method; data were obtained through in-depth interviews with Ceu Epik and two of her TikTok followers, along with observations of the @ceuepik TikTok account, and documentation. The findings show that Ceu Epik’s self-concept as a food influencer was shaped by her evolution from a housewife with a culinary hobby into a local content creator who consistently upholds Sundanese cultural identity. This identity is expressed through the stage name “Ceu Epik”, the use of the Sundanese language in her voice-overs, and the signature slogan “Bismillah Huapkeun”. Her content management on TikTok follows three approaches: conceptual, spontaneous, and collaborative content. Through these strategies, Ceu Epik not only promotes local culinary heritage but also contributes to its preservation.